A framework for the analysis of vibrations of structures with uncertain attachments. (September 2016) - Li, Shuo; Mace, Brian R.; Ferguson, Neil S.; Halkyard, Roger
Abstract: Attachments affect the dynamic response of an assembled structure. When engineers are modelling structures, small attachments will often not be included in the "bare" model, especially in the initial design stages. The location of these attachments might be poorly known, yet they affect the response of the structure. This paper considers how attachments jointed to the structure at uncertain points, can be included in the dynamic model of a structure. Two approaches are proposed. In the time domain, a combination of component mode synthesis, characteristic constraint modes and modal analysis gives a computationally efficient basis for subsequent analysis using, for example, Monte Carlo simulation. The frequency domain approach is based on assembly of frequency response functions of bare structure and attachment. Numerical examples of a beam and a plate with a point mass added at an uncertain location are considered and predictions compared with experiment results.